1980
DOI: 10.1088/0022-3727/13/11/004
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependent TSC peak in poly(N-vinylcarbazole)

Abstract: A theory of the thermally stimulated current (TSC) transport peak, developed recently, predicts thickness dependence of the maximum temperature of the peak. The experimental observation of this effect, found for the high-temperature TSC peak in poly(N4nylcarbazole) is presented and discussed in terms of dispersive transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Among other things, it was shown that the shape of the 'IX curve and the temperature for which the maximum of the TSC peak occurs should depend not only on the heating rate but also on the sample thickness and the field strength (even if high-field effects, such as the Poole-Frenkel one, are absent). This prediction was verified experimentally for poly(N-vinylcarbazole) [21], polyphenylquinoxaline [22] and crystalline anthracene doped with phenothiazine [23]. Recently, 'TSC drift measurements' were carried out for polymethylphenylsilane [24,25].…”
Section: Introductionmentioning
confidence: 82%
“…Among other things, it was shown that the shape of the 'IX curve and the temperature for which the maximum of the TSC peak occurs should depend not only on the heating rate but also on the sample thickness and the field strength (even if high-field effects, such as the Poole-Frenkel one, are absent). This prediction was verified experimentally for poly(N-vinylcarbazole) [21], polyphenylquinoxaline [22] and crystalline anthracene doped with phenothiazine [23]. Recently, 'TSC drift measurements' were carried out for polymethylphenylsilane [24,25].…”
Section: Introductionmentioning
confidence: 82%
“…After illumination several TSC runs were performed at different electric fields: 1 x 10 6, 1.96 x 10 6, 3.61 x 10 6, 7.78 x 10 6, 1.36 x 10 7 and 2.10 x 107 V/m. In previous papers [15,16] it was also shown that the photoinduced TSC spectra in PVK are due to the transport of the photogenerated carriers through the sample. The higher is the drifting field the larger is the charge area involved.…”
Section: Application To Poly-n-vinyl Carbazolmentioning
confidence: 95%